2020
DOI: 10.1200/po.19.00399
|View full text |Cite
|
Sign up to set email alerts
|

CDK12-Altered Prostate Cancer: Clinical Features and Therapeutic Outcomes to Standard Systemic Therapies, Poly (ADP-Ribose) Polymerase Inhibitors, and PD-1 Inhibitors

Abstract: PURPOSE In prostate cancer, inactivating CDK12 mutations lead to gene fusion–induced neoantigens and possibly sensitivity to immunotherapy. We aimed to clinically, pathologically, and molecularly characterize CDK12-aberrant prostate cancers. METHODS We conducted a retrospective multicenter study to identify patients with advanced prostate cancer who harbored somatic loss-of-function CDK12 mutations. We used descriptive statistics to characterize their clinical features and therapeutic outcomes (prostate-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 24 publications
(39 reference statements)
7
146
1
1
Order By: Relevance
“…We also show that PCa with CDK12 biallelic alterations associate with higher Gleason scores and shorter survival from diagnosis, although we did not observe any differences in outcome on abiraterone/enzalutamide which has been previously reportedmaybe due to the retrospective nature of our investigation [29,30].…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…We also show that PCa with CDK12 biallelic alterations associate with higher Gleason scores and shorter survival from diagnosis, although we did not observe any differences in outcome on abiraterone/enzalutamide which has been previously reportedmaybe due to the retrospective nature of our investigation [29,30].…”
Section: Discussioncontrasting
confidence: 45%
“…We also show for the first time that PCa with biallelic CDK12 aberrations are predominantly enriched for CD4 + FOXP3cells with these tumors surprisingly not having [32,33], with some of these cells being reported to express high PD-1 (4PD1hi) and being able to inhibit cytotoxic T cell function in a PD-1/PD-L1 dependent fashion as well as limit immunotherapy antitumor activity [32]. The data herein suggest that CD4 + FOXP3cells, which CDK12-altered PCa seem to be enriched for, might have an immunosuppressive role, associating with worse survival and might be relevant to immunotherapy trials as a biomarker of interest [30,[34][35].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A recently conducted multicenter trial in patients with advanced PCa with loss of function CDK12 mutations evaluated the efficacies of the poly (ADP-ribose) polymerase and PD-1 inhibitors. Three of eight (38%) patients with CDK12-mutated mCRPC had a significant PSA decline, with a median PFS of 6.6 months [93]. The ongoing IMPACT (NCT03570619) trial is investigating whether this subtype of mCRPC is more susceptible to a combination of ICIs consisting of ipilimumab and nivolumab followed by nivolumab monotherapy [94].…”
Section: The Utilization Of Genomic Selection For Checkpoint Inhibitomentioning
confidence: 99%
“…Another retrospective multicenter study identified 60 patients with at least monoallelic CDK12 alterations. In this series, nine patients who had CDK12 alterations were treated with either pembrolizumab or nivolumab, of whom 33.3% (3/9) had a PSA response and a median PFS of 5.4 months [ 87 ]. This suggests CDK12 deficiency contributes to impaired HRR and has been shown to associate with immunotherapy response.…”
Section: Main Textmentioning
confidence: 99%